Investigating the Role of Positive Parenting in Mitigating Adolescent Disruptive Behaviors in Religious Education - Khan, Yusrah; Tabbasum, Maryum (Annals of Human and Social Sciences, 2025)
This research aims to investigate the impact of various forms of religious education on adolescents’ perceived parenting styles and disruptive behavior. A quantitative research design employing a comparative correlational approach was utilized to collect data from adolescents (N = 300) with the age range of 12-18 years. Convenient purposive sampling technique was employed to gather data from those participants who are exposed to any form of religious education, to explore their parental perceptions and behavioral tendencies. The findings of this research give light to different parenting dimensions that have an effect on the adolescent’s disruptive behavior & facilitate the field of Psychology by giving a new perspective towards religion and religious education along with their association with parenting and maladaptive behavior. Future studies can work on collecting samples from different cities and people of different backgrounds to strengthen the analysis